The Strength of Evidence (Certificate) in Land Rights Disputes According to Government Regulation No. 24 of 1997 Concerning Land Registration - Gabriella Talenta Sekotibo (Journal of Human Rights, Culture and Legal System, 2021)
The purpose of this study is to provide legal certainty and to resolve disputes over land rights ownership for buyers who are acting in good faith when purchasing and selling inheritance. The research method is normative juridical, employing both a statutory and case-based approach. According to the study's findings, buyers with good intentions receive legal protection in the form of compensation. However, when parties with bad intentions violate Article 1267 of the Civil Code, the legal consequences of buying and selling inherited land are null and void, as they contain elements of fraud, oversight, and ignorance. additional heirs. Keeping in mind that the property being traded is inheritance land that already possesses permanent legal standing and cannot be traded without the approval of other heirs.Keywords: Legal Protection; Good Faith Buyers; and Inheritance Land.